Book review: The Indian Legal Profession in the Age of Globalization: The Rise of Corporate Legal Sector and Its Impact on Lawyers and Society. Edited by David B. Wilkins, Vikramaditya S. Khanna, and David M. Trubek, Cambridge University Press, New Delhi. (January 2019) - Sharma, Prakash
The Indian Legal Profession in the Age of Globalization: The Rise of Corporate Legal Sector and Its Impact on Lawyers and Society. Edited by David B. Wilkins, Vikramaditya S. Khanna, and David M. Trubek, Cambridge University Press, New Delhi, 2018 (South Asian Edition). xv + 756 pp., (Paperback), ₹895. ISBN: 978-1-108-44487-3